The physiology of mosquitoes - Clements, A. N. (Alan Neville) (International series of monographs on pure and applied biology. Division, Zoology, 1963)
Pure and Applied Biology, Volume 17: The Physiology of Mosquitoes explores some physiological aspects of mosquitoes, including their development, metabolism, survival, reproduction, and behavior. This book is composed of 16 chapters, and begins with discussions on the early life of mosquitoes, larval nutrition, excretion, respiration, and the osmotic and ionic regulation of body fluids. The succeeding chapters deal with different factors affecting the growth and metamorphosis of mosquitoes; the structure and function of their circulatory system; survival and longevity; adult mosquito feeding,